2013
DOI: 10.1016/j.jval.2012.08.2213
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis: Stress Ulcer Bleeding Prophylaxis with Proton Pump Inhibitors, H2 Receptor Antagonists

Abstract: PPI prophylaxis is the most efficient prophylactic strategy in patients at high risk of developing SUB when compared with using H2RAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 56 publications
1
36
0
7
Order By: Relevance
“…For instance, up to 10% of general practitioner (GP) consultations in the UK are for dyspepsia (6). The prescribing of PPIs has increased in recent years with studies showing them to be more effective than H2 antagonists in both preventing and healing ulcers as well as reducing GI bleeds (7)(8)(9)(10)(11)(12)(13). This is important if patients are on long term treatment such as NSAIDs for pain or a combination of antiplatelet and anti-coagulant treatment (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, up to 10% of general practitioner (GP) consultations in the UK are for dyspepsia (6). The prescribing of PPIs has increased in recent years with studies showing them to be more effective than H2 antagonists in both preventing and healing ulcers as well as reducing GI bleeds (7)(8)(9)(10)(11)(12)(13). This is important if patients are on long term treatment such as NSAIDs for pain or a combination of antiplatelet and anti-coagulant treatment (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…SUP is most often used for stress-induced ulcer bleeding prevention, e.g., stomach acid neutralizer (antacid), proton pump inhibitor (PPI), histamine-2 receptor antagonist, sucralfate, and misoprostol. The previous studies were conducted by Harty and Ancha [6], Schupp et al [7], Barkun et al [8], and Barletta and Sclar [9] proved that PPI was more effective among all prophylactic agents in preventing stress ulcer bleeding.…”
Section: Introductionmentioning
confidence: 94%
“…PPIs and H2RAs present different pharmacological efficacies in preventing stress ulcer bleeding in the ICU. One study found that the probabilities of stress ulcer bleeding and ventilator‐assisted pneumonia were 1.3% and 10.3%, respectively, for PPIs versus 6.6% and 10.3%, respectively, for H2RAs [7]. In one systematic review and meta‐analysis of 1720 patients admitted to ICUs, PPIs were more effective than H2RAs at reducing overt UGIB (relative risk, 0.35; 95% confidence interval, 0.21–0.59; p < 0.0001; I = 15%).…”
Section: Conflicts Of Interestmentioning
confidence: 99%